A Postmodern Riddle?: Gaps, Inferences and Mark’s Abrupt Ending - Iverson, Kelly R. ca. 20./21. Jh. (Journal for the study of the New Testament, 2022)
It is widely acknowledged that Mark’s abrupt ending (16.8) is best understood as a deliberate narrative device. Despite this ‘new consensus’, a number of scholars continue to assert that this approach is not only problematic but also depends on a postmodern perspective that overemphasizes the reader/audience. This article argues that Mark’s ending has been crafted in order to invoke a predictive inference that encourages the interpreter to imagine events beyond the concluding scene of the narrative. In dialogue with the cognitive sciences, it is argued that the inferential processes that govern this activity have been shaped by evolutionary developments. Although the new consensus has often been articulated in conversation with modern literary theory, there is an underlying, cognitive basis for the approach that has seldom been appreciated by NT scholars.